Accuracy of Sonographic Chorionicity Classification in Twin Gestations. (1st December 2014) - Blumenfeld, Yair J.; Momirova, Valerija; Rouse, Dwight J.; Caritis, Steve N.; Sciscione, Anthony; Peaceman, Alan M.; Reddy, Uma M.; Varner, Michael W.; Malone, Fergal D.; Iams, Jay D.; Mercer, Brian M.; Thorp, John M.; et al.
Abstract : Objectives: To evaluate the accuracy of sonographic classification of chorionicity in a large cohort of twins and investigate which factors may be associated with sonographic accuracy. Methods: We conducted a secondary analysis of a randomized trial of preterm birth prevention in twins. Sonographic classification of chorionicity was compared with pathologic examination of the placenta. Maternal (age, body mass index, diabetes, and hypertension), obstetric (prior cesarean delivery, gestational age at the first sonographic examination, and antepartum bleeding), and sonographic (oligohydramnios, polyhydramnios, and twin‐twin transfusion syndrome) factors were assessed for their possible association with accuracy. Results: A total of 545 twin sets in which chorionicity was classified by sonography before 20 weeks' gestation were included; 455 were dichorionic and 90 were monochorionic based on pathologic examination. Sonography misclassified 35 of 545 twin pregnancies (6.4%): 18 of 455 dichorionic twins (4.0%) and 17 of 90 monochorionic twins (19.0%). The sensitivity and specificity of sonographic diagnosis of monochorionicity were 81.1% and 96.0%, respectively. In a multivariable analysis, pregnancies with initial sonographic examinations before 14 weeks' gestation were less likely to have misclassified chorionicity than those with sonographic examinations at 15 to 20 weeks (odds ratio [OR], 0.47; 95% confidence interval [CI], 0.23–0.96). For each week increase in gestational age, the odds of misclassification rose by 10% (OR, 1.10; 95% CI, 1.01–1.2). In the multivariable analysis, maternal age, body mass index, parity, and prior cesarean delivery were not associated with sonographic accuracy. Conclusions: Sonography before 20 weeks incorrectly classified chorionicity in 6.4% of twin gestations. Those with first sonographic examinations performed at earlier gestational ages had improved chorionicity diagnosis.